Application of rigid-perfectly plastic spectra in improved seismic response assessment by Endurance Time method. (15th March 2016) - Foyouzat, M.A.; Estekanchi, H.E.
Highlights: Rigid-Perfectly Plastic (RPP) spectra is applied in Endurance Time (ET) analysis. RPP proves to be a more versatile measure of intensity as nonlinearity increases. Optimal design of standard and friction damper equipped steel frame is demonstrated. This method has good potential for multilevel response history based optimization. Abstract: The Endurance Time (ET) method is a dynamic analysis procedure in which structures are subjected to predesigned accelerograms that increase their intensity in time. The main advantage of the ET method over the standard time-history analysis, which uses ground motions as excitation, is its reduced computational effort. In this paper, the nonlinear rigid-perfectly plastic (RPP) spectra, instead of linear elastic spectra, are used to correlate the seismic hazard return period and the time in the ET analysis. Several elastic-perfectly plastic SDOF systems as well as two three-story steel frames—namely a moment-resisting frame and a frame equipped with friction dampers—are analyzed. The response curves obtained by this procedure are compared with the ones obtained by implementing nonlinear time-history analysis. Twenty-two recorded ground motions, which are scaled to multiple intensity levels, are employed to develop the response curves in the time-history method. The results suggest that applying the RPP spectra as the intensity measure is more appropriate for the intensity levels corresponding to large return periods, where the structure is expected to experience significant plastic deformations. However, for small return periods, where the structure experiences slight plastic deformations, elastic spectra provide an effective intensity measure.